Pengaruh Tangibility, Profitabilitas, Growth Opportunity, dan Ukuran Perusahaan terhadap Struktur Modal : (Studi Empiris pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Rahayu Dwi Anggraini; Indah Rahayu Lestari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the influence of tangibility, profitability, growth opportunity, and company size on capital structure. The object of this study consists of companies in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023. The sampling technique used in this study is purposive sampling method, and a total of 53 companies in the property and real estate sector that met the sampling criteria were obtained. The analysis technique used is multiple linear regression analysis using SPSS software version 22.0. The results of this study indicate that the tangibility and company size variables have a positive and significant influence on capital structure, while profitability has a negative and significant influence on capital structure. Meanwhile, the growth opportunity variable has no significant influence on capital structure.